PEMETAAN PARTISIPATIF DAN MONITORING PENGELOLAAN KEBUN KEMENYAN MASYARAKAT DESA HUTA PAUNG KECAMATAN POLLUNG - Jonson Lumban-Gaol; Bisman Nababan; Riza Aitiando Pasaribu; Muhammad; Ni Putu Ratna Suhita (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2023)
The community has managed the benzoin forest in Paung Village, Pollung District, for hundreds of years, but the land ownership status is state land. In line with government programs to involve the community in forest management, such as by establishing social forests, it is necessary to conduct preparations such as mapping the boundaries of community forest management. In this community service activity, the boundaries of community benzoin forest management have been mapped with the application of geospatial technology, namely the integration of remote sensing satellite technology and the Global Positioning System (GPS) to determine boundary coordinates. Boundary mapping of the benzoin forest was carried out in a participatory manner by directly involving the community who had conducted activities in the benzoin forest. Based on mapping the boundaries of the Benzoin forest management area, the average area managed by the community is around 2 ha per family. The monitoring results around the benzoin forest show decreased vegetation cover. But the vegetation land cover in the Benzoin forest management area of ​​the Paung village Forest Village community has not changed. The benzoin forest area of ​​the Puang village community is maintained since the community uses benzoin resin, so trees are not cut down.